A Detailed Analysis of GPS Live‐Sky Signals Without a Dish. Issue 4 (December 2014) - York, Johnathan; Joplin, Andrew; Bratton, Michael; Munton, David
ABSTRACT This paper explores a premise that, with appropriate application of digital signal processing techniques, much of the detailed signal analysis typically associated with a dish can instead be done with a standard low‐gain GNSS antenna. To do so, the signals of the recently launched GPS IIF satellites are examined, with particular attention on the L5 signal. Notably, using a high‐quality non‐directional GNSS antenna, we demonstrate observations of: (1) signal bandpass and dispersive characteristics, (2) chip shape, (3) eye and constellation diagrams, and (4) millisecond‐level transient events. Such observations are enabled by use of the computationally efficient GNSS Complex Ambiguity Function (GCAF) technique. The methods used to process the GCAF data to produce these results are discussed in detail, with careful attention to the limitations of the techniques. Qualitative comparisons are made to similar dish‐based measurements found in open literature. Copyright © 2014 Institute of Navigation.